2017
DOI: 10.15694/mep.2017.000221
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based medicine skills that last: A transferable model utilizing integration, spaced learning, and repetition with a single study design among second-year medical students

Abstract: Introduction. The medical education literature lacks descriptions of evidence-based medicine (EBM) curricula with competency-based learning outcomes. The objective of this report is to describe an approach to designing, implementing, and assessing long-term learning in an integrated second-year EBM curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…The EBM OSCEs were designed by the EBM theme lead in collaboration with the Assessment Lead and external EBM experts. Issues relating to faculty development was not unique to our setting, it has been identified as a challenge in the delivery of effective EBM curriculum in other medical schools [25]. However, our study has shown that with a strong commitment from a medical school, close collaborative working and a supportive learning environment it is feasible to integrate EBM into the assessment strategy of a medical school.…”
Section: Discussionmentioning
confidence: 92%
“…The EBM OSCEs were designed by the EBM theme lead in collaboration with the Assessment Lead and external EBM experts. Issues relating to faculty development was not unique to our setting, it has been identified as a challenge in the delivery of effective EBM curriculum in other medical schools [25]. However, our study has shown that with a strong commitment from a medical school, close collaborative working and a supportive learning environment it is feasible to integrate EBM into the assessment strategy of a medical school.…”
Section: Discussionmentioning
confidence: 92%
“…These are based on the idea that skill of forming memory can be improved if the process of long-term potentiation is reinforced by practising recall, spacing, testing and interleaving. 34,35 Combined, these strategies can help set the foundation for a sound clinical knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The course was designed and delivered by the EBM theme lead who has been a champion and brought in support from few clinicians and external EBM experts. Issues relating to faculty development was not unique to our setting, it has been identi ed as a challenge in the delivery of effective EBM curriculum in other medical schools (25). To address the challenge of faculty development and availability of trained EBM educators, we have tried innovative methods such as use of technology to record our sessions; passive teaching methods relying on student engagement and peer mentoring from students and recent graduates who have also helped in developing YouTube videos.…”
Section: Discussionmentioning
confidence: 99%